2020
DOI: 10.3390/jcm9113674
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Liquid Biopsy in Decision-Making for Patients with Non-Small Cell Lung Cancer

Abstract: Liquid biopsy is a rapidly emerging tool of precision oncology enabling minimally invasive molecular diagnostics and longitudinal monitoring of treatment response. For the clinical management of advanced stage lung cancer patients, detection and quantification of circulating tumor DNA (ctDNA) is now widely adopted into clinical practice. Still, interpretation of results and validation of ctDNA-based treatment decisions remain challenging. We report here our experience implementing liquid biopsies into the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 91 publications
2
5
0
Order By: Relevance
“…Although most patients in the ALK-positive cohort had tissue available for local biomarker analysis, this was not the case for all patients, and several patients were reported to have inadequate or insufficient tissue for biomarker testing. This highlights the role for bloodbased assays in selecting patients for targeted therapy, as previously suggested by Akhoundova et al 24 The numerically higher investigator-assessed confirmed ORR reported in BFAST (87.4% [95% CI: 78.5-93.5]) versus ALEX (71.7% [95% CI: 63.8-78.7]) suggests that patient populations selected by means of blood-based NGS assay and tissue-based IHC/FISH may differ slightly. 17 population, and these patients derived less clinical benefit than those with concordant results.…”
Section: Discussionsupporting
confidence: 67%
“…Although most patients in the ALK-positive cohort had tissue available for local biomarker analysis, this was not the case for all patients, and several patients were reported to have inadequate or insufficient tissue for biomarker testing. This highlights the role for bloodbased assays in selecting patients for targeted therapy, as previously suggested by Akhoundova et al 24 The numerically higher investigator-assessed confirmed ORR reported in BFAST (87.4% [95% CI: 78.5-93.5]) versus ALEX (71.7% [95% CI: 63.8-78.7]) suggests that patient populations selected by means of blood-based NGS assay and tissue-based IHC/FISH may differ slightly. 17 population, and these patients derived less clinical benefit than those with concordant results.…”
Section: Discussionsupporting
confidence: 67%
“…Detection of small cell transformation should not be delayed, and timely tissue sampling performed, whenever there is clinical or radiological suspicion and irrespective of liquid biopsy results. Also, the possibility of false positive liquid biopsy results caused by clonal hematopoiesis, which can involve genes mutated in lung cancer (like TP53 and KRAS), or a mutation from a secondary independent malignancy should be kept in mind [ 43 , 45 ].…”
Section: Predictive Biomarker Testing For Targeted Treatmentmentioning
confidence: 99%
“…The presence of this mutation justifies the administration of osimertinib, while the absence of this substitution calls for other treatment options. Re-biopsy of multiple visceral tumor lumps is often not feasible; therefore, the analysis of EGFR T790M mutation usually relies on liquid biopsy[ 24 , 25 ]. Clinical studies demonstrate that the detection of EGFR T790M mutation in plasma is seriously compromised by the low sensitivity of the test, especially in patients with limited tumor burden[ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%